Home‐care workers' experiences of assisting people with dementia with their personal care: A qualitative interview study. (31st May 2021) - Backhouse, Tamara; Ruston, Annmarie
Abstract: Home‐care workers are increasingly caring for clients living with dementia. Workers usually have limited dementia training and are low paid and often lone working. Little is known about how home‐care workers assist people with dementia with their personal care. We aimed to explore the experiences of home‐care workers and the knowledge and skills they rely on when providing personal care to people with dementia. In 2020, we conducted 17 semi‐structured, face‐to‐face interviews with home‐care workers in the East of England. Analysis was inductive and thematic. Two key themes were present in the data: 'structural conditions' and 'clients' dementia‐related characteristics'. For each of these, we examined the challenges faced by home‐care workers and the strategies they used to manage these challenges. Challenges included time allocation for visits, completing care plan tasks, lone working, communication and understanding, refusals of care, and client behaviours. To mitigate these challenges, home‐care workers utilised system support, time management, training and experience and enacted a caring relationship, thought about their approach, and used distraction and communication skills. Workers relied on skills such as, relationship building, team working, observation, communication, decision making and interpersonal sensitivity. They drew on knowledge about the person, the person's needs, their own abilities, company policies and procedures and their role and responsibilities as a home‐care worker. Home‐care workers had more scope to mitigate client‐based challenges by adapting care within client interactions, than to manage structural challenges where there was a limit to what workers could do. Despite a commissioning focus on time‐ and task‐based care, when caring for people with dementia, home‐care workers used interaction as a way to bring the person along and complete care activities. Home‐care services should acknowledge the importance of interactions with people with dementia within home care and support their workers to develop interpersonal sensitivity.